Book Reviews (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
• African muckracking: 75 Years of investigative journalism in Africa; Anya Schiffrin & George Lugalambi• The rise of Africa’s middle class: Myths, realities and critical engagements; Henning Melber• Teaching and learning History and Geography in the South African classroom; Elize van Eeden & Pieter Warnich (Editors) Aubrey Golightly (Consulting Editor)